Untargeted Alternative Routes of Arbovirus Transmission - Pompon, Julien (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Arboviruses have become global threats. Common to Dengue, Zika, yellow fever, chikungunya, and Mayaro viruses is their ability to be transmitted by mosquitoes. Several strategies based on transgenics or microbiology are currently being field-tested. While this approach seems hopeful, the research community needs to focus on potential backlash from these technologies to prevent failure. The aim of the Special Issue is to cover different transmission routes that are untargeted by the newly developed strategies to foresee limitations. Here, Fontenille & Powell gave their insights on how a mosquito species becomes a global vector, Yen & Failloux presented the limitations of Wolbachia-based population replacement, Pereira-dos-Santos et al. reviewed the evidence that Aedes albopictus is an important vector, and Diagne et al. gathered information about the latest emerging arbovirus: Mayaro. Manuel et al. demonstrated that in certain conditions mosquitoes efficiently transmit Zika viruses and Rozo-Lopez et al. showed that midges vertically transmit stomatitis virus, highlighting the epidemiological significance of vertical transmission. Vector competence for secondary vectors was improved by Kosoltanapiwat et al. during entomological surveillance and by Fernandes et al. when evaluating different vector species competence for Zika viruses. Morales-Vargas et al. and Calvez et al. improved our understanding of DENV2 and DENV4 epidemiology.